Workshop on Modification and Innovation of Processed Banana Products by the MBKM Program of Indo Global Mandiri Students - Sadana, Afdan Mifta; Hertati, Lesi; Asharie, Asmawati (International Journal of Social Science and Community Service, 2023)
Natural resources are resources acquired from the environment and can be utilized to fulfill human needs. One agricultural commodity that is abundant in this region is bananas. However, bananas that are sold directly tend to have a lower price and cannot be stored for a long time after being harvested due to their rapid ripening process, which leads to spoilage. Therefore, diversifying the product is necessary, and one way to do this is by processing bananas into chips. In this endeavor, we utilized the ABCD (Asset Based Community Development) method. Our activities aim to support the MBKM 2023 program, with a focus on creating positive change around km 20 Palembang. The assistance process involves several steps, starting from studying scenarios, uncovering the past (discovery), envisioning the future (dream), planning actions (design), engaging in participatory action (define), and finally monitoring and evaluating activities (destiny). By utilizing easily accessible raw materials, such as bananas, and adding innovative flavors, we hope to enhance the community's skills and creativity, as well as provide entrepreneurial opportunities to increase the selling value of bananas. The evaluation results indicate that the banana chip business is profitable, with an R/C ratio of 3.4. However, further evaluation and assistance in overall marketing strategy are still required.